2020
DOI: 10.1111/exd.14169
|View full text |Cite
|
Sign up to set email alerts
|

IL6R is a target of miR‐197 in human keratinocytes

Abstract: Psoriasis is one of the most common chronic inflammatory skin disorders, with cutaneous and systemic manifestations and substantial negative effects on affected patients' quality of life. [1] MicroRNAs (miRNAs) are post-transcriptional regulators of gene expression. [2] Recent studies have revealed that interactions between miRNAs and their targets play critical roles in regulating distinct signalling pathways during skin differentiation. [3,4] Evidence is rapidly accumulating for the roles of miRNAs in the pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 68 publications
0
5
0
Order By: Relevance
“…MiRNAs are widely found in many species, and their application in genomics provides many therapeutic advantages for gene regulation of psoriasis. Differentially expressed miRNAs may be involved in the pathogenesis of psoriasis through mediating cell proliferation, inflammation, and immunity via regulating the levels of downstream target genes and signaling pathways [26, 27]. In this study, we further investigated the mechanism of XIST/miR-338-5p in psoriasis.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…MiRNAs are widely found in many species, and their application in genomics provides many therapeutic advantages for gene regulation of psoriasis. Differentially expressed miRNAs may be involved in the pathogenesis of psoriasis through mediating cell proliferation, inflammation, and immunity via regulating the levels of downstream target genes and signaling pathways [26, 27]. In this study, we further investigated the mechanism of XIST/miR-338-5p in psoriasis.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…The assay was performed on SCL-II cells. Cells were grown in the presence of 100 μM 4-thiouridine (4SU) for 24 h and processed as described in Masalha et al [ 60 ]. Ago2 PAR-CLIP data were deposited in NCBI’s Gene Expression Omnibus, GEO accession number GSE155538.…”
Section: Methodsmentioning
confidence: 99%
“…Simondurairaj et al reported an increase in IL-6R expression in gastric cancer, indicating that IL-6R may be both a therapeutic target and a prognostic marker of gastric cancer [35]. Overexpression of both IL-6 and IL-6R has been observed in patients with psoriasis [36,37]. It is therefore possible that blocking the action of TNF-a by adalimumab affects only the expression of IL-6, not its receptor IL-6R.…”
Section: Nevertheless Biesemann Et Al Demonstrated In Anmentioning
confidence: 99%